2012
DOI: 10.1111/j.1521-0391.2012.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Homeless Youth Who Use Cocaine and Methamphetamine

Abstract: This cross-sectional hepatitis health promotion study (N = 156) was designed to identify correlates of cocaine and methamphetamine use, among young, homeless persons living in Los Angeles County. Structured questionnaires were administered at baseline to assess sociodemographic characteristics, drug history and social support. Unadjusted analysis showed that older age, having a history of incarceration, injection drug use (IDU), 10 or more sexual partners and sex for money were associated with both cocaine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 31 publications
5
37
1
Order By: Relevance
“…However, 30 % of all homeless adults report a foster care history, compared to 4 % of the general public (Courtney and Piliavin 1998;Reilly 2003), and research has shown that between 11 and 36 % of the foster youth population experiences homelessness (Dworsky et al 2012). Recent research has begun to demonstrate high rates of substance use and problem behaviors (Courtney et al 2011;Hudson and Nandy 2012;Nyamathi et al 2012). Because social networks have been shown to affect some behavioral health outcomes for both homeless youth and former foster youth (Bao et al 2000;Halkitis et al 2013;Joseph et al 2014;Kidd 2003;Rice et al 2007; Rice and Rhoades 2013;Rice et al 2008) and studies have begun to discover the role that foster care plays in network disruption, a need exists to better understand the network characteristics of homeless young adults with a history of foster care and associations between these characteristics and behavioral health outcomes in this population.…”
Section: Introductionmentioning
confidence: 99%
“…However, 30 % of all homeless adults report a foster care history, compared to 4 % of the general public (Courtney and Piliavin 1998;Reilly 2003), and research has shown that between 11 and 36 % of the foster youth population experiences homelessness (Dworsky et al 2012). Recent research has begun to demonstrate high rates of substance use and problem behaviors (Courtney et al 2011;Hudson and Nandy 2012;Nyamathi et al 2012). Because social networks have been shown to affect some behavioral health outcomes for both homeless youth and former foster youth (Bao et al 2000;Halkitis et al 2013;Joseph et al 2014;Kidd 2003;Rice et al 2007; Rice and Rhoades 2013;Rice et al 2008) and studies have begun to discover the role that foster care plays in network disruption, a need exists to better understand the network characteristics of homeless young adults with a history of foster care and associations between these characteristics and behavioral health outcomes in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, the CHSCP has guided studies on HIV and hepatitis risk, and health outcomes among drug-abusing and homeless adults (Nyamathi et al, 2007; Nyamathi, Hudson, Greengold, & Leake, 2012; Nyamathi, Stein, Dixon, Longshore, & Galaif, 2003; Stein & Nyamathi, 2004) and among ex-offenders (Nyamathi et al, in press). In this framework, an inclusion of antecedent factors such as type of facility incarcerated (jail vs prison), type of drug used and whether single or poly drug pattern, age, education, and mental health history) were of interest in our study.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of substance use and alcohol use, ever, in a Denver cohort of 186 homeless youth and young adults (Van Leeuwen et al, 2004) was alcohol (69%), marijuana (75%), methamphetamine (18%), cocaine (19%), heroin 180 C N C N C N C N Volume 42, Issue 2, October 2012 © eContent Management Pty Ltd detail elsewhere (Nyamathi, Hudson, Greengold, & Leake, 2012).…”
Section: Introductionmentioning
confidence: 99%